Wood treatment by paraffin impregnation - preliminary research - Esteves, B. (2012)
Pinus pinaster wood was impregnated with paraffin to different levels using a hot-cold process with the hot step at 170-180 ºC and 2-4h. Weight gain, density, equilibrium moisture and dimensional stability (ASE) at 35% and 65% relative humidity and termite durability against Reticulitermes grassei (Clément) were determined. The weight gain (WG) ranged between 16% and 87% according to treatment. It was determined that 30 minutes in the cold bath was enough to reach maximum penetration. Density increased from 0.57 to 0.99, almost reaching the water density. ASE ranged between 38-96% and 16-71% for respectively 35% and 65% relative humidity. The best anti shrinking efficiency (ASE) was obtained for a combined treatment at 180 ºC (4h) and 61% WG. Nevertheless the use of a higher temperature bath did not significantly improve the dimensional stability when compared at the same paraffin WG. Equilibrium moisture content decreased drastically due to the treatment from 9.9%, 12.0% to 0.5% and 2.1% for 35% and 65% relative humidity. Termite durability improved from level 4 to level 3 of attack. Treated wood presented higher termite mortality (52%) against (17%) of untreated wood. The preliminary tests with paraffin impregnation showed that wood has lower equilibrium moisture, higher dimensional stability and density and a higher resistance against termites.